Eksistensialisme sebagai Landasan Metafisika Worldview Islam: Analisis Gagasan Al-Attas tentang Wujud - Aulia Rakhmat (University of Darussalam Gontor, Indonesia, 2022)
This study aims to examine the idea of al-Attas' existentialism which is embodied in his conception of wujud and its relationship with worldview. Al-Attas' definition of worldview, the Islamic vision of Wujūd, indicates the significance of wujūd in the worldview building formulated by al-Attas. However, al-Attas's conception of wujūd is overlooked in academic studies, even though this concept is a crucial theme in his philosophical thinking. This study applies descriptive and analytical methods as well as a philosophical approach to analyze al-Attas' works. This paper argues that al-Attas's idea of worldview is built on the principle of existentialism which is inspired by the concept of Waḥdah al-Wujūd Sufism. It states that wujūd is the true reality, while what is called quiddity or essence is just a mode of wujūd. Thus, the structure of reality is Wujūd in its Unity and Diversity which is nothing but a manifestation of al-Ḥaqq.